2022
DOI: 10.3390/jof8100989
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compound (VOC) Profiles of Different Trichoderma Species and Their Potential Application

Abstract: Fungi emit a broad spectrum of volatile organic compounds (VOCs), sometimes producing species-specific volatile profiles. Volatilomes have received over the last decade increasing attention in ecological, environmental and agricultural studies due to their potential to be used in the biocontrol of plant pathogens and pests and as plant growth-promoting factors. In the present study, we characterised and compared the volatilomes from four different Trichoderma species: T. asperellum B6; T. atroviride P1; T. afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…As might be expected, the PTR-Qi-TOF-MS analysis showed that many VOCs were present in similar abundance in samples from the three T. harzianum strains, not showing significant differences at the two time points considered, such as those putatively identified as decanal, acetaldehyde, 2,4-dimethylfuran, furan, formaldehyde, 1,2,4-trimethylbenzene, 6,10-dimethyl-5,9-undecadien-2-one (geranylacetone), p -cymene, methanethiol, 3-methylacetophenone, 2-methoxy-4-methylphenol (=creosol), sesquiterpenes, ethanol, methanol, hexenal isomeres and cedrol, molecules all known to be normally emitted by different microbes, including Trichoderma spp. [ 18 , 38 , 50 , 72 ]. However, no significant differences in the production levels of 6-PP and its derivatives were detected among the three strains of T. harzianum under the experimental condition of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As might be expected, the PTR-Qi-TOF-MS analysis showed that many VOCs were present in similar abundance in samples from the three T. harzianum strains, not showing significant differences at the two time points considered, such as those putatively identified as decanal, acetaldehyde, 2,4-dimethylfuran, furan, formaldehyde, 1,2,4-trimethylbenzene, 6,10-dimethyl-5,9-undecadien-2-one (geranylacetone), p -cymene, methanethiol, 3-methylacetophenone, 2-methoxy-4-methylphenol (=creosol), sesquiterpenes, ethanol, methanol, hexenal isomeres and cedrol, molecules all known to be normally emitted by different microbes, including Trichoderma spp. [ 18 , 38 , 50 , 72 ]. However, no significant differences in the production levels of 6-PP and its derivatives were detected among the three strains of T. harzianum under the experimental condition of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…To perform VOCs analysis of Trichoderma strains, a 5 mm diameter agar plug with the fungus was placed at the center of a 1 L Erlenmeyer conical glass flask equipped with a GL45 3-valve screw cap, containing 100 mL of PDA. VOCs protonation and measurements of headspace VOC profiles accumulated in the flasks were carried out as previously described [ 38 ]. Four different biological replicates for each sample were analyzed and the measurements were taken at five (half of the agar surface was colonized by the mycelium) and nine (all the agar surface was colonized by the mycelium) days post inoculation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One compound (1‐Nonen‐4‐ol) has been reported to be associated with ozone release (Li et al ., 2018). Notably, 2‐pentyl‐Furan has been reported to change significantly before and after seed germination in some species of Vicia sativa , and the production of this substance by Xylemiaceae promotes spore germination (Gualtieri et al ., 2022; Riley et al ., 2022). Unfortunately, these compounds are currently unavailable, limiting our ability to verify their ecological effect.…”
Section: Discussionmentioning
confidence: 99%